Brachyuran crabs (Crustacea: Decapoda) from the Canary Islands (eastern Atlantic): checklist, zoogeographic considerations and conservation - José Antonio González (Scientia Marina, 2016)
Just 20 years have passed since González (1995) finished one of his seminal works on decapod crustaceans of the Canary Islands, thanks to the help of the reputed carcinologists L.B. Holthuis and C.H.J.M. Fransen. This publication allowed d’Udekem d’Acoz (1999) to include the Canarian decapods in his inventory of the NE Atlantic. No checklists of decapod fauna specifically covering this area have been published since then, and an update is needed. The current list of Canarian brachyuran crabs comprises 132 species. Additional species have been recorded thanks to intensified research into deep water, natural range expansions from nearby areas, introduction by anthropogenic activities and description of new taxa; several of these changes are detailed in this review. Although the description of new brachyuran species is not expected to occur at a significant rate, an increase in the number of species from the Canaries is expected to result from trawling and dredging sampling, as well as from introduction of non-native species. For the first time, some zoogeographic comments on the Canarian brachyuran carcinofauna are made. Finally, crab species of commercial interest are listed, their current threats are identified and some updated conservation measures are proposed.